The Luck of Roaring Camp / Bret Harte. - Harte, Bret; K.E.S.E. (Firm); Kleine (George) Collection (Library of Congress) (New York : Books)
The men of a rough Western mining camp adopt a baby whose mother, a half-breed Indian, dies after having wandered through the winter snows. Three years later the luck of the camp runs out. A half-breed Indian, seeking revenge for having been chased away from the camp, kidnaps the child, but is stopped by the camp gambler. In the ensuing fight, the child is thrust aside and picks up a gold nugget, thus discovering a new vein of gold ore. The half-breed is killed, and all ends happily for the miners.
Copyright: Thomas A. Edison, Inc.; 29Jun17; LP11018.
Edison produced a shorter version of the same title in 1909.
Adapted from the story of the same title by Bret Harte.
A Conquest picture.
Moving picture world
Ivan Christie, Robert Chandler, William Wadsworth, J.C. O'Loughlin, Betty Young, Eugene Field (baby), Thomas Trenor, A. Newson, Al. Stewart, Florence Adams.
Keywords: Physical Geography; Westerns; Adaptations; Shorts